2010
DOI: 10.1021/np900378c
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from Scorzonera austriaca

Abstract: Six new sesquiterpene lactones, scorzoaustriacoside (1), scorzoaustriacin (2), scorzoaustriacin 3-O-beta-d-glucoside (3), 4-epi-dihydroestafiatol (4), 14-isovaleroxyscorzoaustricin (5), and 14-isovaleroxyscorzoaustricin sulfate (6), along with five known guaianolides, were isolated from an acetone extract of the roots of Scorzonera austriaca. The structures of the new compounds were elucidated mainly by interpretation of their 1D and 2D NMR and HRMS data. Several isolates obtained in this investigation were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The positions of both methylenes were also supported by HMBC correlations. The methyl group attached to C-11 appeared at δ = 14.6 in the 13 C NMR spectrum and is α-oriented, while the methyl group at C-11, which is β -oriented, should have a chemical shift of less than 10 ppm [6,9]. The stereochemistry at all the stereogenic centers was confirmed by a NOESY experiment and by comparison with literature data (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…The positions of both methylenes were also supported by HMBC correlations. The methyl group attached to C-11 appeared at δ = 14.6 in the 13 C NMR spectrum and is α-oriented, while the methyl group at C-11, which is β -oriented, should have a chemical shift of less than 10 ppm [6,9]. The stereochemistry at all the stereogenic centers was confirmed by a NOESY experiment and by comparison with literature data (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…The IR spectrum exhibited absorption bands at 3396 -3150, 1760, 1688, and 1625 cm −1 which indicated the presence of a hydroxyl group, a γ-lactone, an α, β -unsaturated cyclopentenone, and a C = C double bond, respectively. The 1 H NMR, 13 C NMR and 2D NMR data indicated that compound 3 is structurally similar to compounds 1 and 2. In compound 3 there is a lack of the side chain on C-8.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…An aliphatic CH group (d(H) 3.49 (dd, J ¼ 9.5, 7.0); d(C) 48.7 (CH)), with 1 H, 1 H-COSY cross-peaks to HÀC(3) and HÀC(30) (Fig. 2), was attributed to HÀC (2). Another aliphatic CH group…”
mentioning
confidence: 97%